Karakteristik Sastra Sufi (Content Analysis Karya-karya Sastra Indonesia) - Lidya Arman (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2019)
Literary work is an inseparable part of human life. Literature appears along with the history of human existence. In fact, it can be said that from the literature produced, it reflected the support of human civilization. As a social institution, literature reflects the expression of appreciation and inner experience of the narrator or the author of certain authors or situations. Literature always experiences development along with changing times and the emergence of new thoughts in every aspect of life. This also applies in the world of literature. Parallel aspects will show a clear picture of literature from the past until now. Methodologically this research uses library research or library research. The object of the study in this study is Sufi literary works. The approach used in this study is descriptive qualitative, in which this study describes not intended to test certain hypotheses. Literary works with religious characteristics will be able to direct readers to make conscience more serious, pious and conscientious in inner consideration. So that religious works make the reader pensive and template.